Downlink capacity analysis in distributed antenna systems - Jun-bo WANG; Jin-yuan WANG; Xi-bin ZHAO; Ming GU; Ming CHEN; Yuan JIAO (Tongxin xuebao)
The downlink capacity was analyzed in distributed antenna systems(DAS).Firstly,a composite channel model was established,which took path loss,lognormal shadowing and Rayleigh fading into account.Then,based on the channel model,both the ergodic capacity and outage capacity were analyzed.After that,considering the distribution of mobile stations(MS)in the system,the approximate analytical expressions of the ergodic capacity and outage capacity were derived by making use of selective diversity(SD)transmission scheme for distributed antennas.Numerical results show that both the two approximate analytical expressions can provide sufficient precision for evaluating the system performance of DAS.